A/B testing as an effective instrument for adaptation of the user interface at the iterative model of developing applications for mobile devices - Y. G. Pavlovich; I. F. Kirinovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Changing the user interface always entails risks of decreasing application ergonomics and user churn. The purpose of this work is to find methods for changing the user interface without the need to use and increase the number of active users. Using Alpha/Beta testing and analysis of application metrics, it is possible to include design in each iteration and remotely manage the application configuration, which improves the user interface of the application. The way to integrate the UI modification and adaptation phase into an iterative software development model is proposed in this article. The successful user interface improvement experiments that have improved application metrics are described. In this work, the problem was highlighted, lack of information and control over user purchases, which negatively affected the number of purchases. A hypothesis is put forward that the user must have an effective visualization and control tool in the application. As a result of the experiment, the hypothesis was confirmed by an increase in the number of purchases and user activity. There was also a data security issue in the application, which put users at risk of data loss. An experiment was conducted to change the default value of user settings, which led to an increase of the positive metrics for using the data reservation functionality. The problem of polling users is also considered, which is an important component in the process of improving the ergonomics of an application. The method of remote user polling was used, which allowed to receive quick feedback from users and quickly respond to requests from users. The result of the work is the confirmation of the hypothesis of changes in the user interface in the cycles of the iterative development model, the positive dynamics of application metrics, as well as the satisfaction of users with the changes.